Spatiotemporal analysis of African swine fever outbreaks on South African smallholder farms, 1993-2018 - (:unkn) unknown (My University, 2022)
Source Agritrop Cirad (https://agritrop.cirad.fr/603378/) * Autres projets (id;sigle;titre): ;;(USA) Unravelling the Effect of Contact Networks & Socio- Economic Factors in the Emergence of Infectious Diseases at the Wild-Domestic Interface//
Keywords: African Research